SAVING IN ISLAMIC BANKS: ENCOURAGEMENT OF ISLAMIC FINANCIAL LITERACY - Fauzi, M.; Dwi Agustin (UIN Raden Mas Said Surakarta, 2023)
Islamic banking in Indonesia has exhibited positive growth, although financial inclusion in the sector remains low at 9.06%. Islamic banks present an alternative for those seeking a financial institution that adheres to Islamic principles. The low level of Islamic financial inclusion is attributable to several factors, including the insufficient level of Islamic financial literacy at 8.93%. This research was a type of field research using a quantitative approach. The data used primary data obtained through the distribution of questionnaires to batik entrepreneurs in the Wiradesa Pekalongan sub-district. Samples were taken as many as 65 respondents based on the Slovin formula. The type of sampling technique used cluster proportional random sampling. The statistical tests used validity test, data reliability test, and t-test (t-test) to test the hypothesis. The results of the research on Islamic financial literacy variables have a positive and significant effect on interest in saving in Islamic banks, the significance value is 0.023 <0.05 and the t value (2,328) > t table (2,000).